'This film was captured as a trophy…': the international context of trophy films. (2nd January 2020) - Tanis, Kristina
ABSTRACT: This article is devoted to the issue of so-called 'trophy films' and their role in Soviet-American relations after WWII. The purpose of this research is to reveal how the cultural competition between the USSR and the USA during the early years of the Cold War led to the emergence of the famous credit line 'This film was captured as a trophy after the Soviet Army defeated Nazi troops near Berlin in 1945', which led to the establishment and widespread use of the concept of trophy films in the public space.